Character Education in Mimpi Sejuta Dolar Novel by Alberthiene Endah - Oktaviantoro Oktaviantoro; Mardian Mardian; Fitri Fitri; Eti Sunarsih (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This descriptive qualitative research focuses his study on the values of character education in Mimpi Sejuta Dolar Novel, and how to implement it in Indonesian language learning. The data of this research are (1) novel excerpts related to character education derived from liver, (2) novel quotations related to character education derived from thought, (3) novel excerpt related to character education derived from sports or kinesthetics, (4) novel excerpts related to character education derived from taste and initiative, and (5) implementation of character education in learning.